Practice of Peritoneal Dialysis Catheter Flushing in Australia and New Zealand: Multi-Center Cross-Sectional Survey. Issue 2 (March 2018) - Cho, Yeoungjee; Boudville, Neil; Palmer, Suetonia C.; Chow, Josephine S.F.; Hawley, Carmel M.; Jose, Matthew D.; MacGinley, Rob; Huang, Louis; Moodie, Jo-Anne; Nguyen, Thu; Robison, Laura; Wong, Jeffrey; et al.
Background: Evidence of effective interventions to prevent peritoneal dialysis (PD) catheter malfunction before first use is presently insufficient to guide clinical care. Regular flushing of the PD catheter (e.g. before PD commencement) has been adopted by some practitioners in the belief that it will prevent catheter obstruction and/or malfunction. The aim of this study was to characterize and evaluate PD catheter flushing practices across Australian and New Zealand PD units. Methods: An on-line survey was distributed to all 62 PD units in Australia (12 August 2016; n = 51) and New Zealand (2 February 2017; n = 11), with questions relating to PD catheter flushing practices, audit, and outcomes. Results: Forty-nine units of variable size (< 16 to > 100 patients) completed the survey (79% response rate). All centers flushed PD catheters at some stage after insertion as routine unit practice. Forty-one units (84%) routinely flushed during periods of PD rest at varying intervals ranging from alternate daily to monthly. The type and volume of solution used to flush varied between units. Units that practised routine flushing of PD catheters were almost twice as likely to audit their catheter-related outcomes (66% vs 38%, p = 0.23) and more likely to have reported blocked catheters in the preceding 12 months (84% vs 0%, p = 0.01) compared with those units that did not routinely flush PD catheters. Thirty units (61%) regularly audited and monitored catheter-related outcomes. Conclusions: This study identified a wide variation in center practices relating to PD catheter flushing. Drawing conclusions about any relationship between flushing practices and clinical outcomes was impeded by the relatively low uptake of regular auditing and monitoring of catheter-related outcomes across surveyed units. Evaluation of the benefits and harms of standardized PD catheter flushing practices on patient outcomes in a randomized trial is needed to guide practice.